2014
DOI: 10.1093/carcin/bgu186
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Nur77-dependent apoptotic pathway by a coumarin derivative through activation of JNK and p38 MAPK

Abstract: Coumarins are plant-derived natural products with a broad range of known pharmacological activities including anticancer effects. However, the molecular mechanisms by which this class of promising compounds exerts their anticancer effects remain largely unknown. We report here that a furanocoumarin named apaensin could effectively induce apoptosis of cancer cells through its activation of Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK). Apoptosis induction by apaensin in cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
2
29
1
Order By: Relevance
“…These findings are consistent with those of a previous report [23]. Recent studies have suggested a key role for p38 MAPK and JNK in mediating pathways leading to apoptosis and growth-inhibitory signals [37,38]. Additionally, p38 MAPK and JNK trigger caspase-3 activation and are also necessary for the phosphorylation of apoptosis-related proteins, including Bax and Bcl-2, in cancer cells [23,39].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Suppressupporting
confidence: 93%
“…These findings are consistent with those of a previous report [23]. Recent studies have suggested a key role for p38 MAPK and JNK in mediating pathways leading to apoptosis and growth-inhibitory signals [37,38]. Additionally, p38 MAPK and JNK trigger caspase-3 activation and are also necessary for the phosphorylation of apoptosis-related proteins, including Bax and Bcl-2, in cancer cells [23,39].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Suppressupporting
confidence: 93%
“…5). Recent research suggests an important role for JNK and ERK in pathways related to apoptosis and growth-inhibitory pathways (27,28). In addition, JNK induces caspase-3 activation and JNK is necessary for the phosphorylation of proteins related to apoptosis in cancer cells, including Bcl-2 and Bax (29).…”
Section: Discussionmentioning
confidence: 99%
“…High level expression of phosphorylated P38 MAPK was detected after TIPE2 up-regulation. Recent studies have suggested a key role for P38 MAPK in mediating pathways leading to apoptosis and growth inhibitory signals [ 23 , 24 ]. Additionally, P38 MAPK triggers the activation of caspase-3, 9 and is also necessary for the phosphorylation of apoptosis-related proteins, including Bax, Bim and Bcl-2 in OA-treated cancer cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%